Fragile Communities and Craft Practices: A European Perspective - Padovani, Clio; Whittaker, Paul (Making Futures Journal, 2013)
In this submission we address the theme of Craft as Social Practice through textile craft activities located in regional European textile production. The focus of the enquiry will be provided by two case studies produced through Plustex, an INTERREG IVC project, at University of Southampton. The Plustex research team is investigating qualitative data and good practice examples in the European textile and clothing sector with the aim of supporting its fragile communities and helping to sustain a trade in crisis. The objective of the project is to propose to European policymakers textile specific strategies that might shape a more competitive future for the European textiles industry. The Plustex project’s methodology is anchored on six themes that include increasing creativity in market production, eco-innovation, and enterprise associations. The thematic framework offers the opportunity to investigate many examples of good practice in the textiles industry. Research already completed suggests two examples of current practice that exemplify well the discourse of craft as a facilitator of positive social change. Teixidors is a co-operative of weavers based in Terrassa, outside Barcelona, which produces one-off, luxury home and fashion accessories. Founded in 1983, the company has a clear social vocation. It aims to improve the economic independence and social integration for people with learning difficulties while maintaining the tradition of local textile skills. The exceptional products benefit from hand weaving, artisan practices, tools and attitudes but, most importantly, the humanity of the maker. At Teixidors each weaver is encouraged to select materials with which they have sympathy, build familiarity with their equipment, and according to their character and physique. In this way gender, strength and sensibility inflect the textile to create products with unique features; collections differentiated by the individuality of the maker: a maker embedded in his or her community. In Scotland, after a period of serious decline, the Harris Tweed cottage industry has repositioned itself as a protected brand. Harris Tweed is a unique product produced in the Outer Hebrides by weavers who work in their own homes. The industry supports an employment cluster of around 140 self-employed weavers, and a network of artisans and designers that produce niche designs and products for a growing international market. Synonymous with longevity and heritage, Harris Tweed is increasingly both the skilled expression of a local community and the foundation of that community’s future. Teixidors and the producers of Harris Tweed demonstrate not only a shared commitment to ethical, resilient and indigenous community building but also a debt to historical practices. Between them, they amply demonstrate the transformative practice of craft textiles as an agent for social change and economic success.